Powder-liquid dental resin-reinforced glass ionomer cement composition
By adding specific polymerizable monomers and acid-reactive glass powder to dental resin-reinforced glass ionic watermentin composition, combined with multiple polymerization mechanisms, the problems of white turbidity, water absorption and poor storage stability in the early stage of curing are solved, and the problem of water absorption and expansion and storage stability is achieved. High surface curability, low water absorption and good color resistance.
Patent Information
- Application Number
- CN202010224685.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-24
- Filing Date
- 2020-03-26
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-03-26
AI Technical Summary
The existing dental resin-reinforced glass ionic watermentin compositions are prone to whitening when exposed to moisture in the initial stage of curing, absorb water and expand, and have poor storage stability, which affects the aesthetics and functionality of repair.
Adding acid reactive glass powder, polymerizable monomers containing acid groups, (meth)acrylate-based polymerizable monomers with hydroxyl groups, and (meth)acrylamide-based polymerizable to the composition by adding to the composition to the composition Monomers, combined with photopolymerization and chemical polymerization mechanisms, improve surface curability and color resistance, and optimize the ratio of polymerized monomers to improve storage stability.
The surface curability of the composition is significantly improved, water absorption and expansion are reduced, color resistance is enhanced, and long-term storage stability is ensured, ensuring the aesthetics and functionality of the repaired parts.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a dental filling resin-reinforced glass ionomer cement composition for repairing a tooth partially damaged in shape due to caries, fracture, etc., or a dental bonding resin-reinforced glass ionomer cement composition for bonding or adhering a dental prosthesis to a tooth damaged in shape. More specifically, it relates to a powder-liquid dental filling resin-reinforced glass ionomer cement composition or a powder-liquid dental bonding resin-reinforced glass ionomer cement composition, which exhibits high surface curability even under wet conditions, and thus is unlikely to cause white turbidity on the surface even when exposed to water in the initial stage of curing, and the cured product exhibits high mechanical properties, less water absorption and expansion, and excellent coloration resistance, and is also excellent in storage stability. Background Art
[0002] In dental clinics, in order to restore the aesthetics and functionality of teeth that have been partially damaged due to caries, fractures, etc., direct restoration is performed by filling the teeth with dental composite resins or dental glass ionomer cements, or indirect restoration is performed by bonding or adhering dental prostheses to the teeth using dental adhesive resin cements or dental bonding glass ionomer cements.
[0003] Generally speaking, the dental resin material represented by dental filling composite resin, dental adhesive resin cement etc. is mainly composed of various filling materials such as matrix resin, glass filler or organic-inorganic composite filler and polymerization initiator consisting of multiple polymerizable monomers, and is cured by photopolymerization and / or chemical polymerization. Dental resin material has high mechanical properties, excellent aesthetic properties based on high transparency, and in the material with light curing property, also has the advantage of operability, that is, the operator can make the composition be cured at the desired moment of the operator by light irradiation, etc., Therefore, it has been widely used in recent years. However, many dental resin materials do not have the self-adhesive property to tooth texture, and when these materials are used, it is necessary to share dental primer (primer) and / or dental bonding agent (bonding), and the operation is complicated. And if the tooth surface has residual moisture, then the dental primer and / or dental bonding agent significantly decline the permeability and curability of tooth texture, so it is very important to be moisture-proof when using them. Therefore, in cases where moisture protection is difficult, there is a concern that poor adhesion may occur due to the influence of moisture. In addition, the preventive effect of secondary caries by sustained release of fluoride ions has been observed only in some commercial products.
[0004] In contrast, dental glass ionomer cements represented by dental filling glass ionomer cements and dental bonding glass ionomer cements usually use polycarboxylic acid, water, and acid-reactive glass powders represented by fluoroaluminosilicate glass as main components, and are cured by an acid-base reaction between polycarboxylic acid and acid-reactive glass powder. Dental glass ionomer cements exhibit self-adhesive properties through the action of the polycarboxylic acid in the components, so they have the advantage of not requiring the use of dental adhesives or dental primers. In addition, since the components contain water, they can also be applied to areas that are difficult to prevent moisture, such as root caries. Moreover, fluoride ions are continuously released from the cured product, so the preventive effect of secondary caries can be expected. On the other hand, dental glass ionomer cements have lower mechanical properties than dental resin materials, so their indications are limited to the repair of areas that are difficult to be subjected to stress. In addition, dental glass ionomer cement is opaque, so when dental filling glass ionomer cement is filled into a hole, or when dental bonding glass ionomer cement is used to bond a translucent dental prosthesis to a part of a tooth with damaged morphology, the color compatibility with the tooth or dental prosthesis is low, and there are still problems in terms of aesthetics. Moreover, dental glass ionomer cement cures slowly, so during the few minutes until the curing reaches a certain level, the operator cannot perform subsequent operations such as morphological correction / grinding and removal of excess cement. In addition, if it comes into contact with water at the initial stage of curing, the surface may sometimes become turbid.
[0005] On the other hand, in order to compensate for the various defects existing in dental resin materials and dental glass ionomer cements, a dental resin-reinforced glass ionomer cement has been proposed, which can be cured by utilizing multiple mechanisms of photopolymerization and / or chemical polymerization and acid-base reaction by combining the component composition of dental resin materials and the component composition of dental glass ionomer cement.
[0006] For example, Japanese Patent Application Laid-Open No. 1-308855 discloses a dental resin-reinforced glass ionomer cement composition, which contains a polycarboxylic acid having a polymerizable group, an acid-reactive powder (fluoroaluminosilicate glass powder, etc.), water, a polymerizable monomer (2-hydroxyethyl methacrylate, etc.) and a photopolymerization initiator, and can be cured by utilizing two mechanisms of photopolymerization and acid-base reaction.
[0007] Japanese Patent Gazette No. 3288698 discloses a dental resin-reinforced glass ionomer cement composition, which comprises a polycarboxylic acid, an acid-reactive powder, water, a (meth)acrylate polymerizable monomer, and a photopolymerization initiator and a chemical polymerization initiator as polymerization initiators, and can be cured by three mechanisms of photopolymerization, chemical polymerization and acid-base reaction.
[0008] Japanese Patent Application Laid-Open No. 2014-152179 proposes a dental resin-reinforced glass ionomer cement composition in which the adhesiveness to tooth structure is improved by further adding a polymerizable monomer having an acidic group.
[0009] The dental resin reinforced glass ionomer cement composition shown above has the advantages of both dental glass ionomer cement and dental resin materials, and has long-term sustained fluoride release and higher transparency than existing dental glass ionomer cement. In addition, when light-curable, the composition can be cured at the time desired by the operator by light irradiation, so unlike existing dental glass ionomer cement, it has the advantage of not needing to wait for curing. Moreover, by giving the polymerizable monomer curability based on free radical polymerization, it is relatively difficult to cause the problem of existing dental glass ionomer cement that cures only by acid-base reaction, that is, white turbidity on the surface caused by contact with water in the early stage of curing.
[0010] However, since the dental resin reinforced glass ionomer cement composition contains water that does not contribute to polymerization curing, the curability of the polymerizable monomer based on free radical polymerization is low, and the curability is still insufficient on the surface further inhibited by oxygen. Therefore, the cured product of the dental resin reinforced glass ionomer cement composition is easy to color. In addition, the dental resin reinforced glass ionomer cement composition contains a hydrophilic polymerizable monomer as a main component in consideration of the compatibility with the water contained in the composition, so it interacts with the low polymerization curability, so that the water absorption of its cured product is large, and thus has a tendency to increase water absorption and expansion. Moreover, further improvement is also required for the surface turbidity caused by contact with water in the initial stage of curing.
[0011] In addition, since the pH of the liquid material of the dental resin reinforced glass ionomer cement composition containing polycarboxylic acid and water is low, the coexisting polymerizable monomer is hydrolyzed and various problems arise. Specifically, when the (meth)acrylate polymerizable monomer, which is the most commonly used in dental materials, is used as the polymerizable monomer, the ester bond of the (meth)acrylate group is hydrolyzed to generate methacrylic acid or acrylic acid with high polymerization activity, thereby causing problems in storage stability, such as gelation of the liquid material during storage or reduction in mechanical properties of the cured product. In particular, when the liquid material contains a polymerizable monomer having an acidic group, the trend is significant.
[0012] On the other hand, a technique of applying a (meth)acrylamide-based polymerizable monomer that is hardly hydrolyzed to various dental materials is disclosed.
[0013] For example, Japanese Patent Gazette No. 4171600 discloses a technique for obtaining various dental materials that are difficult to be hydrolyzed even in the presence of an acidic group-containing polymerizable monomer and have excellent storage stability by applying a di- to pentafunctional (meth)acrylamide-based polymerizable monomer. However, in these patent documents, there is no suggestion of the effect obtained when the (meth)acrylamide-based polymerizable monomer is applied to a dental resin-reinforced glass ionomer cement composition, except for improving the storage stability. In addition, there is no record of the structure and number of functional groups of a (meth)acrylamide-based polymerizable monomer suitable for use in a dental resin-reinforced glass ionomer cement composition. Summary of the invention
[0014] For existing dental resin reinforced glass ionomer cement, by imparting photopolymerization and / or chemical polymerization, it is difficult to cause the white turbidity on the surface of the cured product caused by contact with moisture in the initial stage of curing, but it cannot be said that it has been fully improved, and it is expected to further improve the surface curing property. In addition, the water absorption expansion of the cured product is large, so due to the floating of the restoration, the patient will feel uncomfortable, and sometimes there is a danger of deterioration of the occlusion with the opposing teeth. Moreover, the property of being easy to color is still not improved, and the repaired part cannot be kept beautiful for a long time. For this reason, the problem of the present invention is to provide a dental resin reinforced glass ionomer cement composition, which can maintain the excellent characteristics of the existing dental resin reinforced glass ionomer cement composition, and further improve the surface curing property, show less water absorption expansion and excellent coloring resistance, and can stably show various characteristics for a long time, and the storage stability is also excellent.
[0015] The inventors of the present invention have conducted in-depth research to solve the above problems. As a result, they have found that by adding a (meth)acrylate polymerizable monomer having a hydroxyl group and a (meth)acrylamide polymerizable monomer having a trifunctional or higher function to the basic components of the existing dental resin reinforced glass ionomer cement, i.e., an acid-reactive glass powder represented by fluoroaluminosilicate glass powder, water, a polymer of a polymerizable monomer containing an acidic group represented by polyacrylic acid, a polymerizable monomer, and a polymerization initiator, as polymerizable monomers, the curability of the polymerizable monomer is greatly improved in the presence of water, thereby showing excellent surface curability, and the surface of the cured product is difficult to be colored, and the water absorption and expansion are also reduced. In addition, it has been found that by adding a (meth)acrylamide polymerizable monomer having a trifunctional or higher function, the storage stability of the liquid material is improved, and even when a polymerizable monomer containing an acidic group is added to improve the adhesion to the tooth structure, the excellent storage stability is also shown. Furthermore, it was discovered that when the (meth)acrylate polymerizable monomer having a hydroxyl group contains two monomers, a monofunctional (meth)acrylate polymerizable monomer having a hydroxyl group and a di- to tetrafunctional (meth)acrylate polymerizable monomer having a hydroxyl group, at a specific ratio, and / or when a tetrafunctional or higher (meth)acrylamide polymerizable monomer is added as a trifunctional or higher (meth)acrylamide polymerizable monomer, the surface curability and coloring resistance are further improved, and the water absorption swelling is further reduced, thereby completing the present invention.
[0016] That is, the above-mentioned problems are solved by the dental resin-reinforced glass ionomer cement composition of the present invention, which is composed of a powder material containing (a) acid-reactive glass powder and a liquid material containing (b) water, (c) a polymer of a polymerizable monomer containing an acidic group, (d) a (meth)acrylate-based polymerizable monomer having a hydroxyl group, and (e) a trifunctional or higher (meth)acrylamide-based polymerizable monomer, and at least one of the powder material and the liquid material contains (f) a polymerization initiator.
[0017] In addition, the dental resin-reinforced glass ionomer cement composition of the present invention preferably further comprises (g) an acidic group-containing polymerizable monomer in at least one of the powder material and the liquid material.
[0018] In addition, the polymer of the (c) acidic group-containing polymerizable monomer is preferably a polymer of an α,β-unsaturated carboxylic acid.
[0019] In addition, the (d) (meth)acrylate polymerizable monomer having a hydroxyl group includes two monomers, namely, a monofunctional (meth)acrylate polymerizable monomer having a hydroxyl group and a di- to tetrafunctional (meth)acrylate polymerizable monomer having a hydroxyl group, and the mixing ratio of the monofunctional (meth)acrylate polymerizable monomer having a hydroxyl group to the di- to tetrafunctional (meth)acrylate polymerizable monomer having a hydroxyl group is preferably 1:2 to 4:1 in terms of weight ratio.
[0020] The (e) trifunctional or higher-functional (meth)acrylamide-based polymerizable monomer is preferably a tetrafunctional or higher-functional (meth)acrylamide-based polymerizable monomer.
[0021] The (e) trifunctional or higher-functional (meth)acrylamide-based polymerizable monomer is more preferably a compound represented by the following formula (1).
[0022]
[0023] (Where R 1 represents a hydrogen atom or a methyl group, which may be the same as or different from each other. 2 represents a linear or branched alkylene group having 2 to 6 carbon atoms which may or may not have a substituent and may be the same or different from each other.
[0024] Furthermore, among the compounds represented by formula (1), R 1 All are hydrogen atoms.
[0025] The (e) trifunctional or higher-functional (meth)acrylamide-based polymerizable monomer is more preferably a compound represented by the following formula (2).
[0026]
[0027] (Where R 1 represents a hydrogen atom or a methyl group, which may be the same as or different from each other. )
[0028] Furthermore, among the compounds represented by formula (2), R 1 All are hydrogen atoms.
[0029] The dental resin reinforced glass ionomer cement composition of the present invention also exhibits high surface curing properties under wet conditions. As a result, in cases where it is difficult to remove moisture, surface turbidity due to poor curing is unlikely to occur. Moreover, its cured product exhibits excellent mechanical properties and coloring resistance, so that the initial repair state can be maintained for a long time, and since it has little water absorption and swelling, it is unlikely to cause discomfort during biting due to floating of the repaired product. In addition, since it is also excellent in storage stability, its characteristics can be stably exhibited for a long time. DETAILED DESCRIPTION
[0030] Hereinafter, the present invention will be described in further detail.
[0031] The dental resin-reinforced glass ionomer cement composition of the present invention is composed of a powder material including (a) an acid-reactive glass powder and a liquid material including (b) water, (c) a polymer of a polymerizable monomer containing an acidic group, (d) a (meth)acrylate-based polymerizable monomer having a hydroxyl group, and (e) a trifunctional or higher (meth)acrylamide-based polymerizable monomer, wherein at least one of the powder material and the liquid material contains (f) a polymerization initiator, and optionally at least one of the powder material and the liquid material contains (g) a polymerizable monomer containing an acidic group. It should be noted that in this specification, (meth)acrylate is used to collectively represent both acrylate and methacrylate, (meth)acryloyl is used to collectively represent both acryloyl and methacryloyl, and (meth)acrylamide is used to collectively represent both acrylamide and methacrylamide.
[0032] The (a) acid-reactive glass powder that can be used in the dental resin-reinforced glass ionomer cement composition of the present invention needs to contain an acid-reactive element and fluorine. The acid-reactive glass powder contains the acid-reactive element, and thus undergoes an acid-base reaction with the acidic group of the polymer of the (c) acidic group-containing polymerizable monomer described later in the presence of water. If the acid-reactive element is specifically exemplified, sodium, potassium, calcium, strontium, barium, lanthanum, aluminum, zinc, etc. can be cited, but are not limited to these. One or more of these acid-reactive elements can be contained, and their content is not particularly limited.
[0033] In order to impart X-ray contrast properties to the dental resin-reinforced glass ionomer cement composition of the present invention, it is preferred that an X-ray opaque element be contained in the acid-reactive glass powder. Specific examples of X-ray opaque elements include, but are not limited to, strontium, lanthanum, zirconium, titanium, yttrium, ytterbium, tantalum, tin, tellurium, tungsten, and bismuth. In addition, other elements contained in the acid-reactive glass powder are not particularly limited, and the acid-reactive glass powder in the present invention may contain various elements.
[0034] Examples of the acid-reactive glass powder include aluminosilicate glass, borosilicate glass, aluminoborate glass, boroaluminosilicate glass, phosphate glass, boric acid glass, and silica glass containing the acid-reactive element shown above, fluorine, and an X-ray opaque element, but are not limited to these.
[0035] The shape of the acid-reactive glass powder is not particularly limited, and any particle shape such as spherical, needle-shaped, plate-shaped, crushed, or flaky can be used without any limitation. These acid-reactive glass powders can be used alone or in combination.
[0036] The production method of these acid-reactive glass powders is not particularly limited, and acid-reactive glass powders produced by any production method such as a melting method, a gas phase method, and a sol-gel method can be used without any problem. Among them, it is preferable to use acid-reactive glass powders produced by a melting method or a sol-gel method because the types of elements contained in the acid-reactive glass powder and their contents can be easily controlled.
[0037] The acid-reactive glass powder commonly available on the market as a filling material can be used without being processed such as pulverized, but can be appropriately pulverized and adjusted to a desired average particle size according to the use or purpose of the dental resin-reinforced glass ionomer cement composition of the present invention. There is no particular limitation on the pulverization method, and powder pulverized by any pulverization method in a wet method or a dry method can be used. Specifically, a high-speed rotary mill such as a hammer mill or a turbine mill, a container-driven media mill such as a ball mill or a vibration mill, a media stirring mill such as a sand mill or a stirring type attritor, a jet mill, etc. can be used for pulverization.
[0038] For example, when the dental resin-reinforced glass ionomer cement composition of the present invention is used as a filling material or an abutment construction material, since high mechanical properties are required, the average particle size of the acid-reactive glass powder is preferably in the range of 0.01 to 30.0 μm, more preferably in the range of 0.01 to 10.0 μm.
[0039] When the dental resin-reinforced glass ionomer cement composition of the present invention is used as an adhesive material, a thin film thickness is required, so the average particle size of the acid-reactive glass powder is preferably in the range of 0.01 to 10.0 μm, more preferably in the range of 0.01 to 5.0 μm.
[0040] If the average particle size of the acid-reactive glass powder is less than 0.01 μm, the surface area is large and it cannot be contained in a large amount in the composition, which may cause a decrease in mechanical properties. In addition, the viscosity of the kneaded product may increase, and the workability may deteriorate.
[0041] When used as a filling material or abutment construction material, if the average particle size of the acid-reactive glass powder is greater than 30.0 μm, the surface of the material after grinding becomes rough, which may cause coloration. In addition, when used as an adhesive material, if the average particle size of the acid-reactive glass powder is greater than 10.0 μm, the film thickness becomes thick, so the bonded dental prosthesis floats and the expected fit may not be obtained.
[0042] For the purpose of adjusting the operability, curing characteristics, mechanical characteristics, etc. of the dental resin reinforced glass ionomer cement composition of the present invention, various surface treatments, heat treatments, agglomeration treatments in liquid phase or gas phase, etc., microencapsulation treatments containing the surface with organic matter, or grafting treatments such as surface functionalization using organic matter can be implemented on the acid-reactive glass powder within the range that the acid-base reaction of the polymer of the polymerizable monomer containing an acidic group described later will not be adversely affected. In addition, these treatments can be implemented alone or in combination, and there will be no problem. Among these, it is preferred to implement surface treatment or heat treatment from the aspect of easy control of various characteristics and excellent productivity.
[0043] If the surface treatment method of the acid-reactive glass powder is specifically exemplified, it can be cited that washing is based on an acid such as phosphoric acid or acetic acid, surface treatment is based on an acidic compound such as tartaric acid or polycarboxylic acid, surface treatment is based on a fluoride such as aluminum fluoride, surface treatment is based on a silane compound such as γ-methacryloxypropyltrimethoxysilane or tetramethoxysilane, etc. The surface treatment method that can be used in the present invention is not limited to the above methods, and these surface treatment methods can be used alone or in combination.
[0044] If a specific example of a heat treatment method for the acid-reactive glass powder is given, there can be cited a treatment method of heating at 100 to 800° C. for 1 to 72 hours using an electric furnace or the like. The heat treatment method that can be used in the present invention is not limited to the above method, and there is no problem in performing the heat treatment at a single temperature or at multiple temperatures.
[0045] As for the (b) water that can be used in the dental resin-reinforced glass ionomer cement composition of the present invention, any water can be used without any limitation as long as it does not contain impurities that adversely affect the curability, mechanical properties, etc. of the dental resin-reinforced glass ionomer cement composition. Specifically, distilled water or ion-exchanged water is preferably used.
[0046] As for the polymer of the polymerizable monomer containing an acidic group (c) that can be used in the dental resin reinforced glass ionomer cement composition of the present invention, any polymer obtained by polymerizing a polymerizable monomer containing at least one acidic group in the molecule can be used without any limitation. It should be noted that the polymer of the polymerizable monomer containing an acidic group (c) is preferably formulated in a liquid material, but there is no problem in formulating a part of it in a powder material.
[0047] For the polymerizable monomer containing an acidic group that can be used to obtain the polymer of the polymerizable monomer containing an acidic group, the type of the acidic group is not limited, and a polymerizable monomer having any acidic group can be used. In addition, the number (monofunctional or polyfunctional) and type of the unsaturated groups that can be subjected to free radical polymerization possessed by the polymerizable monomer containing an acidic group can also be used without any restriction.
[0048] Specific examples of the acidic group contained in the acidic group-containing polymerizable monomer include a phosphoric acid group, a pyrophosphate group, a phosphonic acid group, a carboxyl group, a sulfonic acid group, and a thiophosphoric acid group, but the acidic group is not limited to these.
[0049] If the unsaturated group that can be polymerized of the polymerizable monomer containing an acidic group is specifically exemplified, there can be mentioned, but it is not limited to, a (meth)acryloyl group, a (meth)acrylamide group, a styryl group, a vinyl group, an allyl group, etc. Among these unsaturated groups, a (meth)acryloyl group or a (meth)acrylamide group is preferred, and a (meth)acryloyl group is more preferred.
[0050] Furthermore, these acidic group-containing polymerizable monomers may also have other functional groups such as alkyl groups, halogen groups, amino groups, glycidyl groups, and / or hydroxyl groups in the molecule.
[0051] Hereinafter, specific examples of the acidic group-containing polymerizable monomer having a (meth)acryloyl group as an unsaturated group that can be used to obtain the polymer of the (c) acidic group-containing polymerizable monomer are shown.
[0052] Examples of the acidic group-containing polymerizable monomer having a phosphate group include (meth)acryloyloxymethyl dihydrogen phosphate, 2-(meth)acryloyloxyethyl dihydrogen phosphate, 3-(meth)acryloyloxypropyl dihydrogen phosphate, 4-(meth)acryloyloxybutyl dihydrogen phosphate, 5-(meth)acryloyloxypentyl dihydrogen phosphate, 6-(meth)acryloyloxyhexyl dihydrogen phosphate, 7-(meth)acryloyloxyheptyl dihydrogen phosphate, 8-(meth)acryloyloxyoctyl dihydrogen phosphate, 9 ... dihydrogen phosphate, bis[2-(meth)acryloyloxyethyl] phosphate, bis[3-(meth)acryloyloxypropyl] phosphate, bis[4-(meth)acryloyloxybutyl] phosphate, bis[6-(meth)acryloyloxyhexyl] phosphate, bis[8-(meth)acryloyloxyoctyl] phosphate, bis[9-(meth)acryloyloxynonyl] phosphate, bis[10-(meth)acryloyloxydecyl] phosphate, 1, 3-di(meth)acryloyloxypropyl-2-dihydrogen phosphate, 2-(meth)acryloyloxyethylphenyl hydrogen phosphate, 2-(meth)acryloyloxyethyl 2'-bromoethyl hydrogen phosphate, etc., but are not limited to these.
[0053] In addition, examples of the acidic group-containing polymerizable monomer having a pyrophosphate group include bis[2-(meth)acryloyloxyethyl] pyrophosphate, bis[3-(meth)acryloyloxypropyl] pyrophosphate, bis[4-(meth)acryloyloxybutyl] pyrophosphate, bis[5-(meth)acryloyloxypentyl] pyrophosphate, bis[6-(meth)acryloyloxyhexyl] pyrophosphate, bis[7-(meth)acryloyloxyheptyl] pyrophosphate, bis[8-(meth)acryloyloxyoctyl] pyrophosphate, bis[9-(meth)acryloyloxynonyl] pyrophosphate, bis[10-(meth)acryloyloxydecyl] pyrophosphate, bis[12-(meth)acryloyloxydodecyl] pyrophosphate, tris[2-(meth)acryloyloxyethyl] pyrophosphate, and tetrakis[2-(meth)acryloyloxyethyl] pyrophosphate, but are not limited thereto.
[0054] In addition, examples of the acidic group-containing polymerizable monomer having a phosphonic acid group include 5-(meth)acryloyloxypentyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonopropionate, 10-(meth)acryloyloxydecyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonoacetate, 10-(meth)acryloyloxydecyl-3-phosphonoacetate, (meth)acryloyloxyethylphenyl phosphate, etc., but are not limited to these.
[0055] Examples of the acidic group-containing polymerizable monomer having a carboxyl group include (meth)acrylic acid, 2-chloroacrylic acid, 3-chloro(meth)acrylic acid, 2-cyanoacrylic acid, aconitic acid, mesaconic acid, maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, fumaric acid, glutaconic acid, citraconic acid, utraconic acid, 1,4-di(meth)acryloyloxyethylpyromellitic acid, 6-(meth)acryloyloxynaphthalene-1,2,6-tricarboxylic acid, 1-butene-1,2,4-tricarboxylic acid, 3-butene-1,2,3-tricarboxylic acid, N-(meth)acryloyl-p-aminobenzoic acid, N-(meth)acryloyl-5-aminosalicylic acid, 4-(Meth)acryloyloxyethyl trimellitic acid and its anhydride, 4-(Meth)acryloyloxybutyl trimellitic acid and its anhydride, 2-(Meth)acryloyloxybenzoic acid, β-(Meth)acryloyloxyethyl hydrogen succinate, β-(Meth)acryloyloxyethyl hydrogen maleate, 11-(Meth)acryloyloxy-1, 1-undecanedicarboxylic acid, p-vinylbenzoic acid, 4-(meth)acryloyloxyethoxycarbonylphthalic acid, 4-(meth)acryloyloxybutoxycarbonylphthalic acid, 4-(meth)acryloyloxyhexyloxycarbonylphthalic acid, 4-(meth)acryloyloxyoctyloxycarbonylphthalic acid, 4-(meth)acryloyloxydecyloxycarbonylphthalic acid and anhydrides thereof, 5-(meth)acryloylaminopentylcarboxylic acid, 6-(meth)acryloyloxy-1,1-hexanedicarboxylic acid, 8-(meth)acryloyloxy-1,1-octanedicarboxylic acid, 10-(meth)acryloyloxy-1,1-decanedicarboxylic acid, 11-(meth)acryloyloxy-1,1-undecanedicarboxylic acid and the like, but are not limited thereto.
[0056] Examples of the acidic group-containing polymerizable monomer having a sulfonic acid group include, but are not limited to, 2-(meth)acrylamide-2-methylpropanesulfonic acid, styrenesulfonic acid, 2-sulfoethyl(meth)acrylate, 4-(meth)acryloyloxybenzenesulfonic acid, and 3-(meth)acryloyloxypropanesulfonic acid.
[0057] In addition, examples of the acidic group-containing polymerizable monomer having a thiophosphorothioate group include 2-(meth)acryloyloxyethyl dihydrogen thiophosphate, 3-(meth)acryloyloxypropyl dihydrogen thiophosphate, 4-(meth)acryloyloxybutyl dihydrogen thiophosphate, 5-(meth)acryloyloxypentyl dihydrogen thiophosphate, 6-(meth)acryloyloxyhexyl dihydrogen thiophosphate, 7-(meth)acryloyloxyheptyl dihydrogen thiophosphate, 8-(meth)acryloyloxyoctyl dihydrogen thiophosphate, 9-(meth)acryloyloxynonyl dihydrogen thiophosphate, and 10-(meth)acryloyloxydecyl dihydrogen thiophosphate, but are not limited to these.
[0058] There is no problem in using the above-mentioned acidic group-containing polymerizable monomers alone or in combination to synthesize polymers of acidic group-containing polymerizable monomers. In addition, there is no problem in synthesizing polymers of acidic group-containing polymerizable monomers by copolymerizing acidic group-containing polymerizable monomers having at least one acidic group in the molecule and polymerizable monomers without acidic groups.
[0059] Among these acidic group-containing polymerizable monomers, it is preferred to use an α,β-unsaturated carboxylic acid-based polymerizable monomer containing an acidic group. The α,β-unsaturated carboxylic acid-based polymerizable monomer containing an acidic group that can be used is not particularly limited, and can be used regardless of the number of carboxyl groups in the molecule, the presence or absence of carboxylic anhydride or other substituents, etc.
[0060] Specific examples of the polymerizable monomers containing acidic groups of these α,β-unsaturated carboxylic acids include (meth)acrylic acid, 2-chloroacrylic acid, 3-chloro(meth)acrylic acid, 2-cyanoacrylic acid, aconitic acid, mesaconic acid, maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, fumaric acid, glutaconic acid, citraconic acid, utraconic acid, tiglic acid, 1-butene-1,2,4-tricarboxylic acid, and 3-butene-1,2,3-tricarboxylic acid, but are not limited thereto.
[0061] There is no particular limitation on the method for polymerizing various polymerizable monomers, and polymers polymerized by any method such as solution polymerization, suspension polymerization, emulsion polymerization, etc. can also be used without any limitation. In addition, in order to obtain the desired polymer, the polymerization initiator and chain transfer agent that can be used during the polymer synthesis can be appropriately selected. The polymers of the polymerizable monomers containing acidic groups thus obtained can be used alone or in combination of multiple types.
[0062] For the polymer of the obtained polymerizable monomer containing an acidic group, for the purpose of adjusting the operating surplus time and the curing time or for the purpose of improving the storage stability, an alkali metal hydroxide such as sodium hydroxide, potassium hydroxide, lithium hydroxide, an alkali metal carbonate such as sodium carbonate, potassium carbonate, lithium carbonate, or an alkali metal bicarbonate such as sodium bicarbonate, potassium bicarbonate, lithium bicarbonate, etc., can be used after a part of the acidic group is subjected to a neutralization reaction. The compounds used for the neutralization are not limited to these, and there will be no problem in using them alone or in combination of multiple types.
[0063] Furthermore, there is no problem that the polymer of the polymerizable monomer containing an acidic group has an unsaturated group that can be subjected to free radical polymerization. However, the polymer of the polymerizable monomer containing an acidic group having an unsaturated group has a relatively low solubility in (b) water, and has a tendency that its amount of compounding becomes low, and thus the mechanical properties of the cured product sometimes decrease, and therefore it is more preferred that the polymer of the polymerizable monomer containing an acidic group does not have an unsaturated group.
[0064] Among these, it is more preferred to use a polymer of a polymerizable monomer containing an acidic group synthesized using only acrylic acid as a starting material (polyacrylic acid); or a copolymer of a polymerizable monomer containing an acidic group synthesized using two or more of acrylic acid and maleic acid, acrylic acid and maleic anhydride, acrylic acid and itaconic acid, acrylic acid and 3-butene-1,2,3-tricarboxylic acid, etc. as starting materials.
[0065] In addition, the weight average molecular weight of the polymer of the polymerizable monomer containing an acidic group is preferably in the range of 10,000 to 500,000, more preferably in the range of 20,000 to 300,000, and further preferably in the range of 20,000 to 200,000. If the weight average molecular weight of the polymer of the polymerizable monomer containing an acidic group is less than 10,000, the mechanical properties of the cured product become too low, and durability may sometimes cause problems. On the other hand, if the weight average molecular weight is greater than 500,000, when the dental resin reinforced glass ionomer cement composition is kneaded, the viscosity of the kneaded product becomes high, and operability may sometimes cause problems.
[0066] The (meth)acrylate-based polymerizable monomer having a hydroxyl group (d) that can be used in the dental resin-reinforced glass ionomer cement composition of the present invention can be used without any limitation as long as it has at least one hydroxyl group in the molecule and at least one (meth)acrylate group as an unsaturated group capable of free radical polymerization.
[0067] Examples of the (meth)acrylate polymerizable monomer having a hydroxyl group include 2-hydroxyethyl (meth)acrylate (2-HEMA), 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, diethylene glycol mono(meth)acrylate, triethylene glycol mono(meth)acrylate, tetraethylene glycol mono(meth)acrylate, polyethylene glycol mono(meth)acrylate, and dipropylene glycol mono(meth)acrylate. Acrylates, polypropylene glycol mono(meth)acrylate, 2,3-dihydroxypropyl (meth)acrylate, glycerol mono(meth)acrylate, erythritol mono(meth)acrylate, addition products of phenols and glycidyl (meth)acrylate, for example, monofunctional (meth)acrylate polymerizable monomers such as 2-hydroxy-3-phenoxypropyl (meth)acrylate and 2-hydroxy-3-naphthoxypropyl (meth)acrylate, 2-hydroxypropyl-1,3-di(meth)acrylate (GDMA), 3-hydroxypropyl-1,2-di(meth)acrylate, bisphenol A glycidyl di(meth)acrylate (Bis-GMA) and polyfunctional (meth)acrylate polymerizable monomers such as 2-hydroxy-3-acryloxypropyl methacrylate (GDA). In addition, polyfunctional (meth)acrylate polymerizable monomers obtained by replacing two or more hydroxyl groups of sugar alcohols (erythritol, arabitol, xylitol, ribitol, iditol, dulcitol, sorbitol, mannitol, etc.), monosaccharides (arabinose, xylose, mannose, galactose, fructose, etc.), disaccharides (sucrose, maltose, lactose, trehalose, etc.), and trisaccharides (maltotriose, raffinose, etc.) with substituents having polymerizable unsaturated groups can be preferably used, but are not limited to these.
[0068] Among them, 2-hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, 2,3-dihydroxypropyl (meth) acrylate, bisphenol A glycidyl di(meth) acrylate (Bis-GMA), 2-hydroxypropyl-1,3-di(meth) acrylate (GDMA), and 2-hydroxy-3-acryloyloxypropyl methacrylate (GDA) are particularly preferred. It should be noted that these (meth) acrylate polymerizable monomers having a hydroxyl group can be used in combination of two or more as needed.
[0069] In the dental resin reinforced glass ionomer cement composition of the present invention, (d) the (meth)acrylate polymerizable monomer having a hydroxyl group includes two monomers of a monofunctional (meth)acrylate polymerizable monomer having a hydroxyl group and a di- to tetrafunctional (meth)acrylate polymerizable monomer having a hydroxyl group, and the mixing ratio of the monofunctional (meth)acrylate polymerizable monomer having a hydroxyl group and the di- to tetrafunctional (meth)acrylate polymerizable monomer having a hydroxyl group is preferably 1:2 to 4:1 in terms of weight ratio. By setting the (meth)acrylate polymerizable monomer having a hydroxyl group to such a combination and mixing ratio, (b) water, (c) the polymer of the polymerizable monomer containing an acidic group, and (e) a trifunctional or higher (meth)acrylamide polymerizable monomer described later are easily and uniformly miscible, and therefore, the mechanical properties and transparency after curing can be improved. Moreover, the aforementioned di- to tetrafunctional (meth)acrylate polymerizable monomer having a hydroxyl group is more preferably a difunctional (meth)acrylate polymerizable monomer having a hydroxyl group.
[0070] As for the (e) trifunctional or higher (meth)acrylamide polymerizable monomer that can be used in the dental resin reinforced glass ionomer cement composition of the present invention, any polymerizable monomer having three or more (meth)acrylamide groups in the molecule can be used without any restrictions. It should be noted that when the trifunctional or higher (meth)acrylamide polymerizable monomer does not have an acidic group and / or a hydroxyl group, it is preferred because it is easy to obtain effects in terms of improving surface curability and coloring resistance and reducing water absorption expansion.
[0071] When (e) a trifunctional or higher-functional (meth)acrylamide-based polymerizable monomer is specifically exemplified, there are monomers represented by the following formula (1) and the following formula (3).
[0072]
[0073] (Where R 1 represents a hydrogen atom or a methyl group, which may be the same as or different from each other. 2 represents a linear or branched alkylene group having 2 to 6 carbon atoms which may or may not have a substituent and may be the same or different from each other.
[0074]
[0075] (Where R 1 represents a hydrogen atom or a methyl group. m represents an integer of 2 to 4. n represents an integer of 2 to 4. k represents 0 or 1. 1 , m are the same as or different from each other. )
[0076] More specific examples of the (e) trifunctional or higher-functional (meth)acrylamide-based polymerizable monomer include monomers represented by the following formulae (2) and (4) to (7).
[0077]
[0078] (Where R 1 represents a hydrogen atom or a methyl group, which may be the same as or different from each other. )
[0079]
[0080]
[0081] Among these, tetrafunctional or higher (meth)acrylamide-based polymerizable monomers are preferred, polymerizable monomers represented by the above formula (1) are more preferred, polymerizable monomers represented by the above formula (2) are further preferred, and R represented by the above formula (2) is most preferred. 1 A polymerizable monomer containing only hydrogen atoms.
[0082] As for the (f) polymerization initiator that can be used in the dental resin-reinforced glass ionomer cement composition of the present invention, a known photopolymerization initiator and / or chemical polymerization initiator can be used without any limitation. It should be noted that the (f) polymerization initiator can be mixed with at least one of the powder material and the liquid material as long as the resin component can be sufficiently cured, and various polymerization initiator systems can be used.
[0083] Examples of the photopolymerization initiator include a photopolymerization initiator composed of a photosensitizer and a photosensitizer / photopolymerization accelerator. Specific examples of the photosensitizer include benzyl, camphorquinone, α-naphthyl, acetylnaphthalene, p,p'-dimethoxybenzyl, p,p'-dichlorobenzylacetyl, pentanedione, 1,2-phenanthrenequinone, 1,4-phenanthrenequinone, 3,4-phenanthrenequinone, 9,10-phenanthrenequinone, naphthoquinone and other α-diketones; benzoin, benzoin methyl ether, benzoin ethyl ether and other benzoin alkyl ethers; thioxanthones such as 2-chlorothioxanthone, 2-methylthioxanthone, 2-isopropylthioxanthone, 2-methoxythioxanthone, 2-hydroxythioxanthone, 2,4-diethylthioxanthone and 2,4-diisopropylthioxanthone; benzophenones such as benzophenone, p-chlorobenzophenone and p-methoxybenzophenone; 2,4,6-trimethylbenzoyldiphenylphosphine oxide; bis(2, Acylphosphine oxides such as 4,6-trimethylbenzoyl)phenylphosphine oxide, 2,6-dimethoxybenzoyldiphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)phenylphosphine oxide, α-aminoacetophenones such as 2-benzyl-dimethylamino-1-(4-morpholinophenyl)-butanone-1 and 2-benzyl-diethylamino-1-(4-morpholinophenyl)-propanone-1, ketals such as benzyl dimethyl ketal, benzyl diethyl ketal, benzyl (2-methoxyethyl ketal), 3-(4-methoxybenzoyl)coumarin, 3-benzoyl-5,7-dimethoxycoumarin, 3,3'-carbonylbis(7-diethylaminocoumarin), 3,3'-carbonylbis(7-dibutylaminocoumarin, bis(cyclopentadienyl)-bis[2,6-difluoro-3-(1- Titanocenes such as bis(cyclopentadienyl)-bis(pentanefluorophenyl)-titanium and bis(cyclopentadienyl)-bis(2,3,5,6-tetrafluoro-4-dimethylsilyloxyphenyl)-titanium may be used, but are not limited to these.
[0084] Specific examples of the photopolymerization accelerator include N,N-dimethylaniline, N,N-diethylaniline, N,N-di-n-butylaniline, N,N-dibenzylaniline, N,N-dimethyl-p-toluidine, N,N-dimethyl-m-toluidine, N,N-diethyl-p-toluidine, p-bromo-N,N-dimethylaniline, m-chloro-N,N-dimethylaniline, p-dimethylaminobenzaldehyde, p-dimethylaminoacetophenone, p-dimethylaminobenzoic acid, ethyl p-dimethylaminobenzoate, isoamyl p-dimethylaminobenzoate, methyl N,N-dimethyl-o-aminobenzoate, N,N-dihydroxyethylaniline, N,N-dihydroxyethyl-p-toluidine, p-dimethylaminophenyl alcohol, p-dimethylaminostyrene, N,N-dimethyl-3,5-dimethylaniline, 4- dimethylaminopyridine, N,N-dimethyl-α-naphthylamine, N,N-dimethyl-β-naphthylamine, triethanolamine, tetrabutylamine, tripropylamine, triethylamine, N-methyldiethanolamine, N-ethyldiethanolamine, N,N-dimethylhexylamine, N,N-dimethyldodecylamine, N,N-dimethylstearylamine, methacrylate N,N-dimethylaminoethyl, methacrylate N,N-diethylaminoethyl, 2,2'-(n-butylimino)diethanol and other tertiary amines, N-phenylglycine and other secondary amines, 5-butylbarbituric acid, Barbituric acids such as 1-benzyl-5-phenylbarbituric acid, 1,3,5-trimethylbarbituric acid, sodium 1,3,5-trimethylbarbiturate, and calcium 1,3,5-trimethylbarbiturate; tin compounds such as dibutyltin diacetate, dibutyltin dilaurate, dioctyltin dilaurate, dioctyltin ditert-carbonate, dioctyltin bis(isooctyl mercaptoacetate), and tetramethyl-1,3-diacetoxydistannoxane; aldehyde compounds such as dodecanal and terephthalaldehyde; sulfur-containing compounds such as dodecyl mercaptan, 2-mercaptobenzoxazole, 1-decyl mercaptan, and thiosalicylic acid, etc., but are not limited thereto.
[0085] Furthermore, in order to improve the photopolymerization promoting ability, in addition to the above-mentioned photopolymerization accelerators, adding oxocarboxylic acids such as citric acid, malic acid, tartaric acid, glycolic acid, gluconic acid, α-oxyisobutyric acid, 2-hydroxypropionic acid, 3-hydroxypropionic acid, 3-hydroxybutyric acid, 4-hydroxybutyric acid, and dimethylolpropionic acid is also effective, but is not limited to these.
[0086] As chemical polymerization initiators, there can be mentioned redox polymerization initiator systems composed of peroxide / amine compound, peroxide / amine compound / aromatic sulfinic acid or its salt, or aromatic sulfonyl compound, peroxide / amine compound / (thio)barbituric acid compound or (thio)barbituric acid salt compound, peroxide / amine compound / borate compound, peroxide / ascorbic acid compound, peroxide / thiourea / vanadium compound or copper compound, and organometallic polymerization initiator systems that react with oxygen and water to initiate polymerization. Furthermore, aromatic sulfinic acid salts, borate compounds, and (thio)barbituric acid salts initiate polymerization by causing an acidic compound to act, but are not limited to these.
[0087] Examples of the peroxide include sodium peroxodisulfate, potassium peroxodisulfate, ammonium peroxodisulfate, sodium peroxodiphosphate, potassium peroxodiphosphate, ammonium peroxodiphosphate, benzoyl peroxide, p-chlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, diacetyl peroxide, lauroyl peroxide, di-tert-butyl peroxide, dicumyl peroxide, cumyl hydroperoxide, tert-butyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, tert-amyl hydroperoxide, isopropylbenzene hydroperoxide, 5-phenyl-4-pentenyl hydroperoxide, tert-butyl peroxyisopropyl carbonate, methyl ethyl ketone peroxide, 1,1-bis(tert-butylperoxy)cyclohexane, 1,1-bis(tert-hexylperoxy)cyclohexane, and tert-butyl peroxybenzoate, but are not limited thereto.
[0088] As the amine compound, an aromatic secondary amine or an aromatic tertiary amine is preferred. Specific examples include, but are not limited to, N-methyl-p-toluidine, N-(2-hydroxyethyl)-p-toluidine, ethyl-p-methylaminobenzoate, N-methylaniline, N-(2-hydroxyethyl)aniline, N,N-dimethyl-p-toluidine, N,N-diethyl-p-toluidine, N,N-bis(2-hydroxyethyl)-p-toluidine, ethyl-p-dimethylaminobenzoate, N,N-dimethylaniline, and N,N-bis(2-hydroxyethyl)aniline.
[0089] Examples of the aromatic sulfinic acid or its salt, or the aromatic sulfonyl compound include benzenesulfinic acid, p-toluenesulfinic acid, m-toluenesulfinic acid, 2,4,6-trimethylbenzenesulfinic acid, 2,4,6-triisopropylbenzenesulfinic acid, and sodium salts, potassium salts, lithium salts, or ammonium salts thereof; or benzenesulfonyl chloride, benzenesulfonyl fluoride, benzenesulfonamide, benzenesulfonyl hydrazide, p-toluenesulfonyl chloride, p-toluenesulfonyl fluoride, p-toluenesulfonamide, p-toluenesulfonyl hydrazide, but are not limited thereto.
[0090] Examples of the (thio)barbituric acid compound or (thio)barbiturate compound include barbituric acid, 1,3-dimethylbarbituric acid, 1,3-diphenylbarbituric acid, 1,5-dimethylbarbituric acid, 5-butylbarbituric acid, 5-ethylbarbituric acid, 5-isopropylbarbituric acid, 5-cyclohexylbarbituric acid, 5-dodecylbarbituric acid, 1,3,5-trimethylbarbituric acid, 1,3-dimethyl-5-ethylbarbituric acid, 1,3-dimethyl-n-butylbarbituric acid, 1,3-dimethyl-5-isobutylbarbituric acid, 1,3-dimethyl-5-cyclohexylbarbituric acid, 1,3-dimethyl-5-phenylbarbituric acid, 1-cyclohexyl-5-ethylbarbituric acid, 1-phenyl-5-benzylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, thiobarbituric acid, 1,3-dimethylthiobarbituric acid, 5-phenylthiobarbituric acid and alkali metal salts (lithium, sodium, potassium salts, etc.), alkaline earth metal salts (calcium, strontium, barium, etc.), ammonium salts, tetramethylammonium salts, or tetraethylammonium salts thereof, but are not limited thereto.
[0091] Examples of the borate compound include sodium salts, potassium salts, lithium salts, magnesium salts, tetramethylammonium salts, tetraethylammonium salts, tetrabutylammonium salts, methylpyridinium salts, ethylpyridinium salts, methylquinolate salts, ethylquinolate salts, and the like of trialkylphenylborane, trialkyl(p-chlorophenyl)borane, trialkyl(p-fluorophenyl)borane, trialkyl(p-butylphenyl)borane, trialkyl(p-butoxyphenyl)borane, monoalkyltriphenylborane, monoalkyltri(p-chlorophenyl)borane, monoalkyltri(p-fluorophenyl)borane, monoalkyltri(p-butylphenyl)borane, monoalkyltri(p-butoxyphenyl)borane, tetraphenylborane, tetra(p-chlorophenyl)borane, tetra(p-fluorophenyl)borane, tetra(p-butylphenyl)borane, and tetra(p-butoxyphenyl)borane (the alkyl group is n-butyl, n-octyl, or n-dodecyl), but are not limited thereto.
[0092] Examples of the ascorbic acid compound include, but are not limited to, L(+)-ascorbic acid, erythorbic acid, sodium L(+)-ascorbate, potassium L(+)-ascorbate, calcium L(+)-ascorbate, sodium erythorbate and the like.
[0093] Examples of the thiourea compound include, but are not limited to, 1,3-dimethylthiourea, tetramethylthiourea, 1,1-diethylthiourea, 1,1,3,3-tetraethylthiourea, 1-allyl-2-thiourea, 1,3-diallylthiourea, 1,3-dibutylthiourea, 1,3-diphenyl-2-thiourea, 1,3-dicyclohexylthiourea, ethylenethiourea, N-methylthiourea, N-phenylthiourea, N-benzoylthiourea, and N-acetylthiourea.
[0094] Examples of the vanadium compound include vanadium acetylacetonate, vanadyl acetylacetonate, vanadyl stearate, vanadium naphthenate, and vanadium benzoylacetonate, but are not limited thereto.
[0095] Examples of the copper compound include copper chloride, copper acetate, copper naphthenate, copper salicylate, copper gluconate, copper oleate, copper benzoate, copper acetylacetonate, and copper naphthenate, but are not limited thereto.
[0096] Examples of the organometallic polymerization initiator include organoboron compounds such as triphenylborane, tributylborane, and tributylborane partial oxide, but are not limited thereto.
[0097] These polymerization initiators can be used alone or in combination of two or more regardless of the polymerization mode and polymerization method. In addition, these polymerization initiators can be subjected to secondary treatment such as encapsulation in microcapsules as required without causing any problem.
[0098] For the dental resin reinforced glass ionomer cement composition of the present invention, in order to improve the adhesion to tooth structure, base metals, aluminum oxide and zirconium oxide, etc., (g) a polymerizable monomer containing an acidic group may be contained as required. For the (g) polymerizable monomer containing an acidic group, the same monomer as the polymerizable monomer containing an acidic group that can be used to obtain the polymer of the (c) polymerizable monomer containing an acidic group can be used. In addition, there will be no problem even if the (g) polymerizable monomer containing an acidic group is used alone or in combination of multiple types. It should be noted that the (g) polymerizable monomer containing an acidic group can be incorporated into at least one of the powder material and / or the liquid material.
[0099] Among them, (g) the acidic group-containing polymerizable monomer is preferably a carboxyl group-containing polymerizable monomer, and more preferably has two or more carboxyl groups. By including a carboxyl group-containing polymerizable monomer, it is easy to obtain a dental resin-reinforced glass ionomer cement composition having an excellent balance of adhesiveness to tooth structure and mechanical properties.
[0100] The main components of the dental resin-reinforced glass ionomer cement composition used in the present invention are (a) acid-reactive glass powder, (b) water, (c) polymer of a polymerizable monomer containing an acidic group, (d) a (meth)acrylate polymerizable monomer having a hydroxyl group, (e) a trifunctional or higher (meth)acrylamide polymerizable monomer, (f) a polymerization initiator, and (g) a polymerizable monomer containing an acidic group, and the preferred contents thereof are as follows.
[0101] For (a) acid-reactive glass powder, it is preferred that 20 to 85 parts by weight be contained in 100 parts by weight of the total weight of the composition excluding (f) polymerization initiator. If the content of acid-reactive glass powder is less than 20 parts by weight, the mechanical strength of the cured product becomes too low, and durability may sometimes be problematic. If the content of acid-reactive glass powder is greater than 85 parts by weight, the viscosity of the mixed product becomes high during kneading, and operability may sometimes be problematic. In addition, sometimes curing becomes too fast and sufficient operating margin time cannot be obtained.
[0102] (b) Water is preferably contained in an amount of 1 to 55 parts by weight based on 100 parts by weight of the total weight of the liquid material other than the (f) polymerization initiator. If the water content is less than 1 part by weight, acid-base reaction is difficult to occur, which may sometimes cause poor curing. If the water content is greater than 55 parts by weight, the mechanical strength of the cured product becomes too low, and durability may sometimes cause problems.
[0103] For the polymer of the polymerizable monomer containing an acidic group (c), it is preferred to contain 0.1 to 40 parts by weight in 100 parts by weight of the total weight of the composition excluding the polymerization initiator (f). If the content of the polymer of the polymerizable monomer containing an acidic group is less than 0.1 parts by weight, the acid-base reaction is difficult to occur, which sometimes causes poor curing. If the content is greater than 40 parts by weight, the viscosity of the kneaded material becomes high during mixing, and operability sometimes causes problems. In addition, sometimes the curing becomes faster and sufficient operating margin time cannot be obtained.
[0104] The (meth)acrylate polymerizable monomer (d) having a hydroxyl group is preferably contained in an amount of 3 to 60 parts by weight in 100 parts by weight of the total weight of the polymer of all polymerizable monomers, (b) water, and (c) the polymerizable monomer containing an acidic group. If the content of the (meth)acrylate polymerizable monomer having a hydroxyl group is less than 3 parts by weight, the compatibility of the polymerizable monomers, water, and the polymer of the polymerizable monomer containing an acidic group deteriorates, and the cured product becomes non-uniform, which may sometimes reduce the mechanical properties and transparency. If the content is greater than 60 parts by weight, the curability of the polymerizable monomer mixture deteriorates, and the mechanical properties may sometimes decrease.
[0105] For (e) trifunctional or higher (meth) acrylamide-based polymerizable monomer, it is preferred that 1 to 30 parts by weight be contained in 100 parts by weight of the total weight of the polymer of all polymerizable monomers, (b) water, and (c) acidic group-containing polymerizable monomers. If the content of trifunctional or higher (meth) acrylamide-based polymerizable monomers is less than 1 part by weight, the curability of the polymerizable monomer mixture deteriorates, and the mechanical properties sometimes decrease. In addition, the storage stability sometimes deteriorates. If the content is greater than 30 parts by weight, the compatibility of the polymer of each polymerizable monomer, water, and acidic group-containing polymerizable monomer deteriorates, and the cured product becomes uneven, which sometimes reduces the mechanical properties and transparency.
[0106] (f) The polymerization initiator is preferably added in a ratio of 0.1 to 10 parts by weight relative to 100 parts by weight of the total weight of all polymerizable monomers. If the content of the polymerization initiator is less than 0.1 parts by weight, the curing property may be poor and the mechanical properties may be reduced. If the content is more than 10 parts by weight, the storage stability may be poor.
[0107] The (g) acidic group-containing polymerizable monomer preferably contains 1 to 20 parts by weight in 100 parts by weight of the total weight of the polymer of all polymerizable monomers, (b) water, and (c) acidic group-containing polymerizable monomers. If the content of the acidic group-containing polymerizable monomer is less than 1 part by weight, the adhesion to the tooth structure may be reduced. If the content is more than 20 parts by weight, the curing property may be deteriorated and the mechanical properties may be reduced. In addition, the storage stability may be deteriorated.
[0108] In the dental resin reinforced glass ionomer cement composition of the present invention, polymerizable monomers other than (d) (meth) acrylate polymerizable monomers having a hydroxyl group, (e) (meth) acrylamide polymerizable monomers having trifunctional or higher functions, and (g) polymerizable monomers containing acidic groups may be included for the purpose of improving mechanical properties, as long as it does not adversely affect the various properties. As such polymerizable monomers, known polymerizable monomers can be used without any restrictions on the number (monofunctional or polyfunctional) of unsaturated groups that can undergo free radical polymerization or their types. The following specifically shows the polymerizable monomer having a (meth) acryloyl group as an unsaturated group as a representative example.
[0109] Examples of the monofunctional polymerizable monomer include, but are not limited to, methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, glycidyl (meth)acrylate, dodecyl (meth)acrylate, cyclohexyl (meth)acrylate, allyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, benzyl (meth)acrylate, and isobornyl (meth)acrylate.
[0110] Examples of the aromatic bifunctional polymerizable monomer include 2,2-bis(4-(meth)acryloyloxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytetraethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypentaethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydipropoxyphenyl)propane, 2(4-(meth)acryloyloxyethoxyphenyl)-2(4-(meth)acryloyloxydiethoxyphenyl)propane, 2(4-(meth)acryloyloxytriethoxyphenyl)propane, and 2(4-(meth)acryloyloxydipropoxyphenyl)-2(4-(meth)acryloyloxytriethoxyphenyl)propane. Propane, 2,2-bis(4-(meth)acryloxydipropoxyphenyl)propane, 2,2-bis(4-(meth)acryloxyisopropoxyphenyl)propane, 2,2-bis(4-(meth)acryloxypolyethoxyphenyl)propane, 9,9-bis[4-(2-acryloxyethoxy)phenyl]fluorene, etc. are examples, but are not limited to these.
[0111] Examples of the aliphatic difunctional polymerizable monomer include, but are not limited to, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and 1,10-decanediol di(meth)acrylate.
[0112] Examples of the trifunctional polymerizable monomer include trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, and trimethylolmethane tri(meth)acrylate, but are not limited thereto.
[0113] Examples of the tetrafunctional polymerizable monomer include pentaerythritol tetra(meth)acrylate and ditrimethylolpropane tetra(meth)acrylate, but are not limited thereto.
[0114] Examples of the urethane polymerizable monomer include, but are not limited to, di(meth)acrylates having a urethane bond and difunctional or trifunctional or higher-functional di(meth)acrylates derived from adducts of polymerizable monomers having a hydroxyl group such as 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, and 3-chloro-2-hydroxypropyl(meth)acrylate and diisocyanate compounds such as methylcyclohexane diisocyanate, methylenebis(4-cyclohexylisocyanate), hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, and 4,4-diphenylmethane diisocyanate.
[0115] In addition to the above-mentioned (meth)acrylate group-containing polymerizable monomers, polymerizable monomers having sulfur atoms in the molecule, polymerizable monomers having fluorine groups, oligomers or polymers having at least one polymerizable group can be used. These polymerizable monomers can be used alone or in combination of two or more as needed.
[0116] It should be noted that, as long as the properties of the dental resin-reinforced glass ionomer cement composition of the present invention are not adversely affected, a polymerizable monomer having one or two (meth)acrylamide groups may be contained in the molecule without any problem.
[0117] Preferably, the polymerizable monomers other than (d) a (meth)acrylate polymerizable monomer having a hydroxyl group, (e) a trifunctional or higher (meth)acrylamide polymerizable monomer, and (g) an acidic group-containing polymerizable monomer are contained in an amount of 5.0 parts by weight or less based on 100 parts by weight of the total weight of the liquid material.
[0118] The dental resin-reinforced glass ionomer cement composition of the present invention may contain polycarboxylic acid, phosphoric acid, pyrophosphoric acid or tripolyphosphoric acid for the purpose of controlling the acid-base reaction of the polymer of (a) the acid-reactive glass powder and (c) the polymerizable monomer containing an acidic group and adjusting the operating margin time and the curing time, but is not limited to these.
[0119] If polycarboxylic acids that can be used in the dental resin-reinforced glass ionomer cement composition of the present invention are specifically exemplified, they include tartaric acid, citric acid, maleic acid, fumaric acid, malic acid, aconitic acid, tricarbaryl acid, itaconic acid, 1-butene-1,2,4-tricarboxylic acid, 3-butene-1,2,3-tricarboxylic acid, etc. The polycarboxylic acids described above are not limited to these, and can be used without any limitation.
[0120] These polycarboxylic acids, phosphoric acid, pyrophosphoric acid and / or tripolyphosphoric acid may be used alone or in combination, and are preferably contained in an amount of 0.1 to 15.0 parts by weight based on 100 parts by weight of the total weight of the composition.
[0121] In addition, in the dental resin reinforced glass ionomer cement composition of the present invention, a surfactant may be included for the purpose of improving the mixing property as long as it does not adversely affect the various properties. The surfactant that can be used in the dental resin reinforced glass ionomer cement composition of the present invention may be any of an ionic surfactant and a nonionic surfactant.
[0122] Specific examples of the ionic surfactant include metal salts of aliphatic carboxylic acids such as sodium stearate, metal salts of sulfated aliphatic carboxylic acids such as sodium dioctylsulfosuccinate, and metal salts of higher alcohol sulfates such as sodium stearyl sulfate.
[0123] In addition, as cationic surfactants, amines made of adducts of higher alkylamines and ethylene oxides and lower amines, alkyltrimethylammonium salts such as dodecyltrimethylammonium chloride, etc. In addition, as amphoteric surfactants, metal salts of higher alkylaminopropionic acid such as sodium stearylaminopropionate, betaines such as lauryl dimethyl betaine, etc. can be mentioned.
[0124] In addition, examples of nonionic surfactants include polyethylene glycol or polypropylene glycol types obtained by adding ethylene oxide, propylene oxide and higher alcohols, alkylphenols, fatty acids, higher aliphatic amines, aliphatic amides, etc.; or polyol types in which polyols, diethanolamines, sugars and fatty acids are ester-bonded, etc.
[0125] The surfactants described above are not limited to these and can be used without any restrictions. In addition, these surfactants can be used alone or in combination. Preferably, the surfactant is contained in an amount of 0.001 to 5.0 parts by weight in 100 parts by weight of the total weight of the composition.
[0126] Furthermore, the dental resin-reinforced glass ionomer cement composition of the present invention may contain a non-acid-reactive powder for the purpose of adjusting workability, mechanical properties, or curing properties, as long as the properties are not adversely affected.
[0127] The non-acid-reactive powder that can be used in the dental resin-reinforced glass ionomer cement composition of the present invention can be used without particular limitation as long as it does not contain an element that reacts with an acidic group of a polymerizable monomer containing an acidic group.
[0128] As the non-acid reactive powder, materials known as dental filling materials can be cited, such as inorganic filling materials, organic filling materials, and organic-inorganic composite filling materials, etc., which can be used alone or in combination without any restrictions. Among these, inorganic filling materials are particularly preferably used. In addition, there is no particular limitation on the shape of these non-acid reactive powders, and they can be powders of any particle shape such as spherical, needle-shaped, plate-shaped, crushed, flaky, etc., and their agglomerates, but are not limited to these. There is no particular limitation on the average particle size of these non-acid reactive powders, and it is preferably in the range of 0.001 to 30 μm.
[0129] Specific examples of inorganic fillers include quartz, amorphous silica, ultrafine silica, various glasses that do not contain elements that react with acidic groups (including glasses generated based on a melting method, synthetic glasses generated based on a sol-gel method, glasses generated based on gas phase reactions, etc.), silicon nitride, silicon carbide, boron carbide, etc., but are not limited to these.
[0130] The non-acid-reactive powder is preferably contained in an amount of 0.001 to 40 parts by weight based on 100 parts by weight of the total weight of the composition.
[0131] The dental resin reinforced glass ionomer cement composition of the present invention can be mixed with any known additives as needed. As additives that can be used in the present invention, there can be mentioned polymerization inhibitors, chain transfer agents, colorants, anti-discoloration agents, fluorescent agents, ultraviolet absorbers, antibacterial agents, preservatives, etc.
[0132] [Example]
[0133] The present invention is described in detail below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples. Components (a) to (g) and other components used to prepare the dental resin-reinforced glass ionomer cement compositions of Examples and Comparative Examples and their abbreviations are as follows.
[0134] [(a) Acid-reactive glass powder]
[0135] CK-Si-1: Silane treated fluoroaluminosilicate glass powder 1
[0136] (50% particle size: 4.5 μm)
[0137] CK-Si-2: Silane treated fluoroaluminosilicate glass powder 2
[0138] (50% particle size: 8.0 μm)
[0139] [(b) Water]
[0140] Distilled water
[0141] [(c) Polymer of polymerizable monomer containing acidic group]
[0142] PCA1: Acrylic homopolymer powder (weight average molecular weight: 50,000)
[0143] PCA2: acrylic acid-3-butene-1,2,3-tricarboxylic acid copolymer powder (weight average molecular weight: 80,000)
[0144] PCA3: Acrylic acid-maleic acid copolymer powder (weight average molecular weight: 60,000)
[0145] [(d) (Meth)acrylate-based polymerizable monomer having a hydroxyl group]
[0146] HEMA: 2-Hydroxyethyl Methacrylate
[0147] Bis-GMA: Bisphenol A di(meth)acrylate glycidyl ester
[0148] ·GDMA: Glyceryl dimethacrylate
[0149] ·GDA: 2-Hydroxy-3-acryloxypropyl methacrylate
[0150] [(e) Trifunctional or higher-functional (meth)acrylamide-based polymerizable monomer]
[0151] Tetrafunctional acrylamide polymerizable monomer
[0152] · FAM-401 (manufactured by Fujifilm Corporation): represented by formula (2) and R 1 Compounds consisting entirely of hydrogen atoms
[0153] FAM-402 (manufactured by Fujifilm Corporation): a compound represented by formula (5)
[0154] Trifunctional acrylamide polymerizable monomer
[0155] FAM-301 (manufactured by Fujifilm Corporation): a compound represented by formula (4)
[0156] FAM-302L (manufactured by Fujifilm Corporation): a compound represented by formula (7)
[0157] [(f) Polymerization initiator]
[0158] CQ: dl-Camphorquinone
[0159] DMBE: ethyl p-dimethylaminobenzoate
[0160] DM-3B: N, N-dimethylaminoethyl methacrylate
[0161] ·APO: 2,4,6-trimethylbenzoyldiphenylphosphine oxide
[0162] Bis-APO: Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (Irgacure 819)
[0163] p-TSNa: Sodium p-toluenesulfinate
[0164] ·KPS: Potassium persulfate
[0165] AA: Ascorbic acid
[0166] [(g) Acidic group-containing polymerizable monomer]
[0167] ·4-MET: 4-methacryloyloxyethyl trimellitic acid
[0168] ·4-AET: 4-Acryloyloxyethyl trimellitic acid
[0169] ·10-MDP: 10-methacryloyloxydecyl dihydrogen phosphate
[0170] [other]
[0171] 14EG: Polyethylene glycol #600 dimethacrylate
[0172] ·HEAA: Hydroxyethyl acrylamide
[0173] 2AM: N, N'-methylenebis(methacrylamide)
[0174] The method for producing the fluoroaluminosilicate glass powder is as follows.
[0175] [Manufacturing of Fluoroaluminosilicate Glass Powder 1]
[0176] After mixing various raw materials of silicon dioxide, aluminum oxide, sodium fluoride, and strontium carbonate (glass composition: SiO2 26.4 wt%, Al2O3 29.3 wt%, SrO 20.5 wt%, P2O5 10.9 wt%, Na2O 2.5 wt%, F 10.4 wt%), the raw material mixture was melted in a melting furnace at 1400°C. The melt was taken out from the melting furnace and rapidly cooled in water to obtain glass. The obtained glass was pulverized to obtain fluoroaluminosilicate glass powder 1. The 50% particle size of the glass powder was measured by a laser diffraction particle size analyzer (MICROTRAC MT3300EXII: manufactured by Nikkiso Co., Ltd.), and the result was 4.5 μm.
[0177] [Manufacturing of Fluoroaluminosilicate Glass Powder 2]
[0178] After obtaining glass by the same method as that for the fluoroaluminosilicate glass powder 1, the pulverization time was adjusted to obtain a fluoroaluminosilicate glass powder 2 having a 50% particle size of 8.0 μm.
[0179] The silane treatment method of the fluoroaluminosilicate glass powder is as follows.
[0180] [Silane Treatment of Fluoroaluminosilicate Glass Powders 1 and 2]
[0181] After dispersing 200 g of fluoroaluminosilicate glass powder 1 or 2 in 500 mL of water, 2 g of 3-methacryloxypropyltrimethoxysilane was added and stirred at room temperature for 2 hours. After the solvent was distilled off under reduced pressure, it was dried at 100° C. for 5 hours to obtain silane-treated fluoroaluminosilicate glass powders 1 and 2: CK-Si-1 and CK-Si-2.
[0182] [Preparation of powder materials and liquid materials]
[0183] The respective components were mixed at the ratios shown in Tables 1 to 3 to prepare powder materials and liquid materials of dental resin-reinforced glass ionomer cement compositions used in Examples and Comparative Examples.
[0184] [Table 1]
[0185]
[0186] [Table 2]
[0187] Table 2 Liquid materials used in the examples (parts by weight)
[0188]
[0189] [Table 3]
[0190] Table 3 Liquid materials used in comparative examples (parts by weight)
[0191]
[0192] The dental resin reinforced glass ionomer cement compositions (Examples 1 to 9, Comparative Examples 1 to 6) prepared by mixing the powder materials and liquid materials in the combination and powder / liquid ratio shown in Table 4 were evaluated for surface curability, storage stability, coloration resistance (coloration test), water absorption linear expansion rate, and compressive strength. In addition, the same evaluation was performed on a commercially available dental resin reinforced glass ionomer cement (Fuji II LC (color tone: A2) / GC) (Comparative Example 7). These test results are shown in Table 4. It should be noted that the evaluation method is as follows.
[0193] <Surface curing>
[0194] A stainless steel mold (diameter 10 mm × thickness 0.5 mm: disc-shaped) is placed on a glass plate in a thermostatic chamber set at a temperature of 37°C and a humidity of 100%, and the mixture of the dental resin-reinforced glass ionomer cement composition shown in the embodiment or the comparative example is filled into the mold. The remaining mixture is removed to make the surface flat, and then, with the surface left open, a dental polymerization light irradiator (trade name: Pemblight, manufactured by Matsukaze Co., Ltd.) is used to irradiate light from a height of 5 mm for 10 seconds to solidify the mixture, which is used as a test body. The surface of the test body is rubbed forcefully with a plastic scraper to confirm the presence or absence of damage, the degree of damage, and other surface conditions. Then, water is dripped on the surface, and after leaving it for 1 minute, the water is wiped off with a non-woven fabric, and the surface condition (surface white turbidity) is confirmed again. The evaluation criteria are as follows
[0195] ◎: The surface of the test piece is not sticky, and there is almost no damage or turbidity.
[0196] ○: The surface of the test piece is not sticky, but there are some scratches and part of it is cloudy.
[0197] △: The surface of the test piece is slightly sticky due to the residual unpolymerized polymerizable monomer, and there are some scratches and most of the surface is turbid.
[0198] ×: The surface of the test piece is sticky due to the residual unpolymerized polymerizable monomer, and there are many scratches and overall white turbidity.
[0199] It should be noted that ◎, ○, and △ can tolerate clinical use.
[0200] <Evaluation of storage stability>
[0201] For the dental resin-reinforced glass ionomer cement compositions shown in the examples and comparative examples, the kneading properties were evaluated immediately after preparation. The powder material and the liquid material were stored in a thermostat at 50°C for two months, and the kneading properties were evaluated again and compared with the kneading properties immediately after preparation. The evaluation criteria were as follows.
[0202] A: Almost no change
[0203] B: Mixability decreases
[0204] C: Liquid material separation, gelation, or significant decrease in mixing properties
[0205] It should be noted that A and B can also tolerate clinical use after storage.
[0206] <Coloring test>
[0207] A stainless steel mold (diameter 10 mm×thickness 1 mm: disk-shaped) was placed on a smooth glass plate, and the kneaded product of the dental resin-reinforced glass ionomer cement composition shown in the example or comparative example was filled into the mold. The kneaded product was cured by light irradiation for 10 seconds using a dental polymerization light irradiator (trade name: Pemblight, manufactured by Matsukaze Co., Ltd.), and the cured product was taken out of the mold and used as a test body. Using a colorimeter (Konica Minolta CM-5), the L*, a*, and b* values of the L*a*b* color space were measured on a white plate under the conditions of SCI method, light source D65, and a viewing angle of 2°. After the measurement, the test body was immersed in 5 mL of a 37°C rhodamine solution (0.1%) for 24 hours, then washed with water and dried. After removing the side of the test body (the side of the disk (unpolymerized layer)) with #600 abrasive paper, the L*, a*, and b* values were measured again, and the color difference before and after immersion in the rhodamine solution was calculated by the following formula. Three test pieces were measured for each sample, and the average value was calculated.
[0208] ΔE=((L*1-L*2) 2 +(a*1-a*2) 2 +(b*1-b*2) 2 ) 1 / 2
[0209] The parameters shown on the right side of the formula are as follows.
[0210] L*1: L* value before coloring
[0211] L*2: L* value after coloring
[0212] a*1: a* value before coloring
[0213] a*2: a* value after coloring
[0214] b*1: b* value before coloring
[0215] b*2: b* value after coloring
[0216] In addition, the judgment criteria of the "coloring test" shown in the table are as follows.
[0217] A: ΔE is 0 to less than 40: The test piece is not colored to slightly colored.
[0218] B: ΔE is 40 to less than 50: The test piece is colored to some extent
[0219] C: ΔE is 50 or more: the test piece is obviously colored
[0220] It should be noted that A and B can withstand long-term use in clinical practice. If it is 50 or more, it will be completely incompatible with natural teeth.
[0221] <Water absorption linear expansion ratio>
[0222] A divisible stainless steel mold (4 mm in diameter × 6 mm in height: cylindrical) is placed on a smooth glass plate, and the mixture of the dental resin-reinforced glass ionomer cement composition shown in the embodiment or comparative example is filled into the mold. After the top of the filled mixture is pressed with a smooth glass plate, it is irradiated with light for 10 seconds using a dental polymerization light irradiator (trade name: Pemblight, manufactured by Matsukaze Co., Ltd.) to solidify the mixture. After it is allowed to stand in a constant temperature and humidity chamber at 37°C and a relative humidity of 100% for 1 hour, the solidified material is taken out of the mold and used as a test body. The axial length of the test body is measured using a micrometer (manufactured by Mitutoyo Co., Ltd.) and is used as the initial value. After the test body is immersed in distilled water at 37°C for 24 hours from the end of kneading, the axial length is measured in the same manner and used as the test value. Using the obtained value, the water absorption linear expansion coefficient is calculated by the following formula. Three test bodies are measured for each sample, and the average value is calculated.
[0223] Water absorption linear expansion rate (%) = (test value - initial value) × 100 / initial value
[0224] It should be noted that when the value is less than 1.0, long-term use in clinical practice can be tolerated. If it is greater than 1.0, the tooth root may be fractured.
[0225] <Compression strength test>
[0226] A divisible stainless steel mold (4 mm in diameter × 6 mm in height: cylindrical) is placed on a smooth glass plate, and the mixture of the dental resin-reinforced glass ionomer cement composition shown in the embodiment or comparative example is filled into the mold. After the top of the filled mixture is pressed with a smooth glass plate, it is irradiated with light for 10 seconds using a dental polymerization light irradiator (trade name: Pemblight, manufactured by Matsukaze Co., Ltd.) to solidify the mixture. After it is left to stand in a constant temperature and humidity chamber at 37°C and a relative humidity of 100% for 1 hour, the solidified product is taken out from the mold, and the solidified product after being immersed in distilled water at 37°C for 24 hours from the end of the mixing is used as a test body. According to JIST6609-1 (ISO9917-1), a universal testing machine (Instron 5567A: manufactured by Instron Japan Co., Ltd.) was used to apply a load in the axial direction of a cylindrical test body at a crosshead speed of 1.0 mm / min to measure the compressive strength (MPa). Five test bodies were measured for each sample, and the average value was calculated.
[0227] It should be noted that, as shown in the ISO9917-1 standard, when it is 100 or above, it can be tolerated for clinical use.
[0228] [Table 4]
[0229] Table 4 Evaluation results
[0230]
[0231] As shown in Table 4, the dental resin reinforced glass ionomer cement compositions of Examples 1 to 9 have excellent surface curability and show high compressive strength. In addition, the cured product has less coloration and a low water absorption linear expansion rate. Moreover, the powder material and the liquid material still maintain the miscibility just after preparation after being stored at 50°C for two months. On the other hand, compared with the dental resin reinforced glass ionomer cement compositions of Examples 1 to 9, the dental resin reinforced glass ionomer cement compositions of Comparative Examples 1 to 6 and the commercially available dental resin reinforced glass ionomer cement (Comparative Example 7) are inferior in any of the properties of surface curability, compressive strength, coloration resistance, water absorption linear expansion rate or storage stability.
[0232] In this specification, unless otherwise explained in the context, when a technical feature of the invention is described in either the singular or the plural, or when described without limiting either the singular or the plural, the technical feature may be either the singular or the plural.
[0233] Although the present invention has been described with reference to detailed embodiments, it should be understood by those skilled in the art that various changes or modifications can be made based on the matters disclosed in this specification. Therefore, it is intended that any changes or modifications are included in the scope of the embodiments of the present invention.
[0234] Industrial Applicability
[0235] The dental resin-reinforced glass ionomer cement composition of the present invention can be used for filling and repairing teeth partially damaged in shape due to caries, fractures, etc., and for bonding dental prosthetic devices to teeth damaged in shape.
Claims
1. A dental resin-reinforced glass ionomer cement composition, wherein: The dental resin-reinforced glass ionomer cement composition is composed of a powder material and a liquid material, wherein the powder material contains (a) an acid-reactive glass powder, and the liquid material contains (b) water, (c) a polymer of a polymerizable monomer containing an acidic group, (d) a (meth)acrylate polymerizable monomer having a hydroxyl group, and (e) a trifunctional or higher (meth)acrylamide polymerizable monomer, and at least one of the powder material and the liquid material contains (f) a polymerization initiator. The (d) (meth)acrylate polymerizable monomer having a hydroxyl group comprises two monomers, namely, a monofunctional (meth)acrylate polymerizable monomer having a hydroxyl group and a di- to tetrafunctional (meth)acrylate polymerizable monomer having a hydroxyl group, and the mixing ratio of the monofunctional (meth)acrylate polymerizable monomer having a hydroxyl group to the di- to tetrafunctional (meth)acrylate polymerizable monomer having a hydroxyl group is 1:2 to 4:1 by weight ratio. (a) The acid-reactive glass powder is 20 to 85 parts by weight in 100 parts by weight of the total weight of the composition excluding (f) the polymerization initiator. (b) water is 1 to 55 parts by weight in 100 parts by weight of the total weight of the liquid materials excluding (f) the polymerization initiator, The amount of the polymer of the (c) acidic group-containing polymerizable monomer is 0.1 to 40 parts by weight in 100 parts by weight of the total weight of the composition excluding the (f) polymerization initiator, (d) the (meth)acrylate polymerizable monomer having a hydroxyl group is 3 to 60 parts by weight in 100 parts by weight of the total weight of the polymer of all polymerizable monomers, (b) water and (c) the polymerizable monomer having an acidic group, (e) the trifunctional or higher-functional (meth)acrylamide-based polymerizable monomer is 1 to 30 parts by weight based on 100 parts by weight of the total weight of the polymer of all polymerizable monomers, (b) water and (c) the acidic group-containing polymerizable monomer, (f) 0.1 to 10 parts by weight of a polymerization initiator based on 100 parts by weight of the total weight of all polymerizable monomers; (a) The particle size of the acid-reactive glass powder is in the range of 0.01 μm to 30.0 μm, (c) The weight average molecular weight of the polymer of the acidic group-containing polymerizable monomer is in the range of 10,000 to 500,000.
2. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: At least one of the powder material and the liquid material further includes (g) an acidic group-containing polymerizable monomer.
3. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: The polymer of the (c) acidic group-containing polymerizable monomer is a polymer of an α,β-unsaturated carboxylic acid.
4. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: The (e) trifunctional or higher-functional (meth)acrylamide-based polymerizable monomer is a tetrafunctional or higher-functional (meth)acrylamide-based polymerizable monomer.
5. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: The (e) trifunctional or higher-functional (meth)acrylamide-based polymerizable monomer is a compound represented by the following formula (1): In the formula, R 1 represents a hydrogen atom or a methyl group, which may be the same or different from each other, and R 2 The alkylene groups represent a linear or branched alkylene group having 2 to 6 carbon atoms which may have a substituent and may be the same as or different from each other.
6. The dental resin-reinforced glass ionomer cement composition according to claim 5, wherein: In the compound represented by formula (1), R 1 All are hydrogen atoms.
7. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: The (e) trifunctional or higher-functional (meth)acrylamide-based polymerizable monomer is a compound represented by the following formula (2): In the formula, R 1 represents a hydrogen atom or a methyl group, which may be the same as or different from each other.
8. The dental resin-reinforced glass ionomer cement composition according to claim 7, wherein: In the compound represented by formula (2), R 1 All are hydrogen atoms.
9. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: (a) The acid-reactive glass powder contains one or more acid-reactive elements selected from the group consisting of sodium, potassium, calcium, strontium, barium, lanthanum, aluminum, and zinc.
10. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: (a) The acid-reactive glass powder contains one or more X-ray opaque elements selected from the group consisting of strontium, lanthanum, zirconium, titanium, yttrium, ytterbium, tantalum, tin, tellurium, tungsten, and bismuth.
11. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: (a) The acid-reactive glass powder includes at least one selected from the group consisting of aluminosilicate glass, borosilicate glass, aluminoborate glass, boroaluminosilicate glass, phosphate glass, boric acid glass, and silica glass.
12. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: (a) The shape of the acid-reactive glass powder is one or more selected from the group consisting of spherical, needle-like, plate-like, crushed, and flaky.
13. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: (a) The average particle size of the acid-reactive glass powder is in the range of 0.01 to 10.0 μm.
14. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: (a) The average particle size of the acid-reactive glass powder is in the range of 0.01 to 5.0 μm.
15. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: The acidic group contained in the polymer of the (c) acidic group-containing polymerizable monomer is at least one selected from the group consisting of a phosphoric acid group, a pyrophosphoric acid group, a phosphonic acid group, a carboxyl group, a sulfonic acid group, and a thiophosphoric acid group.
16. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: The polymerizable unsaturated group contained in the polymer of the (c) acidic group-containing polymerizable monomer is at least one selected from the group consisting of a (meth)acryloyl group, a (meth)acrylamide group, a styryl group, a vinyl group, and an allyl group.
17. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: (c) The polymerizable unsaturated group possessed by the polymer of the polymerizable monomer containing an acidic group is one or more selected from the group consisting of (meth)acrylic acid, 2-chloroacrylic acid, 3-chloro(meth)acrylic acid, 2-cyanoacrylic acid, aconitic acid, mesaconic acid, maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, fumaric acid, glutaconic acid, citraconic acid, urconic acid, tiglic acid, 1-butene-1,2,4-tricarboxylic acid and 3-butene-1,2,3-tricarboxylic acid.
18. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: (c) The weight average molecular weight of the polymer of the acidic group-containing polymerizable monomer is in the range of 20,000 to 300,000.
19. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: (c) The weight average molecular weight of the polymer of the acidic group-containing polymerizable monomer is in the range of 20,000 to 200,000.
20. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: (d) The (meth)acrylate-based polymerizable monomer having a hydroxyl group is one or more selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2,3-dihydroxypropyl (meth)acrylate, bisphenol A glycidyl di(meth)acrylate (Bis-GMA), 2-hydroxypropyl-1,3-di(meth)acrylate (GDMA) and 2-hydroxy-3-acryloxypropyl methacrylate (GDA).
21. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: The di- to tetrafunctional (meth)acrylate-based polymerizable monomers having a hydroxyl group are difunctional (meth)acrylate-based polymerizable monomers having a hydroxyl group.
22. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: The (e) trifunctional or higher-functional (meth)acrylamide-based polymerizable monomer is a compound represented by the following formula (4):
23. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: The (e) trifunctional or higher-functional (meth)acrylamide-based polymerizable monomer is a compound represented by the following formula (5):
24. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: The (e) trifunctional or higher-functional (meth)acrylamide-based polymerizable monomer is a compound represented by the following formula (6):
25. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: The (e) trifunctional or higher-functional (meth)acrylamide-based polymerizable monomer is a compound represented by the following formula (7):
26. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: (f) The polymerization initiator is a photopolymerization initiator.
27. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: (f) The polymerization initiator is a chemical polymerization initiator.
28. The dental resin-reinforced glass ionomer cement composition according to claim 2, wherein: (g) The acidic group-containing polymerizable monomer is a carboxyl group-containing polymerizable monomer.
29. The dental resin-reinforced glass ionomer cement composition according to claim 2, wherein: (g) The acidic group-containing polymerizable monomer is a carboxyl group-containing polymerizable monomer having two or more carboxyl groups.
30. The dental resin-reinforced glass ionomer cement composition according to claim 2, wherein: The content of (g) the acidic group-containing polymerizable monomer is 1 to 20 parts by weight based on 100 parts by weight of the total weight of the polymer of all polymerizable monomers, (b) water and (c) the acidic group-containing polymerizable monomer.
31. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: The polymerizable monomers other than (d) a (meth)acrylate polymerizable monomer having a hydroxyl group, (e) a trifunctional or higher functional (meth)acrylamide polymerizable monomer, and (g) an acidic group-containing polymerizable monomer are contained in an amount within a range of 5.0 parts by weight based on 100 parts by weight of the total weight of the liquid material.
32. The dental resin-reinforced glass ionomer cement composition according to claim 1, wherein: (e) The trifunctional or higher-functional (meth)acrylamide-based polymerizable monomer does not have an acidic group and / or a hydroxyl group.
Citation Information
Patent Citations
Double-curable ionomer dental cement
JP1989308855A
Dental resin modified glass-ionomer composition
JP2014152179A
Dental composition
US20140039087A1
Root canal treatment material and root canal treatment kit
US20180296445A1